2022
DOI: 10.15184/aqy.2022.39
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture and use: bone and tooth objects from the Late Bronze Age ‘shaman's grave’ at Przeczyce, Poland

Abstract: The microscopic analysis of tool marks on objects from the Late Bronze Age ‘shaman's grave’ at Przeczyce, Poland, has demonstrated that two wild boar tusk pendants, a bone disc and a set of bone tubes were manufactured exclusively using metal tools. We argue that the tubes were a musical instrument that originally consisted of several separate pieces, rather than a pan flute, as has previously been suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…VII: 5). Boar tusks with two holes, which could have been pendants or were sewn on the clothing, have been found from the grave dated to 900-750 BC in Przeczyce, Poland (Baron et al, 2022), and some pendants made of horse incisors have been found from Sobiejuchy (Harding et al, 2004, p. 64, pl. 28: 36-37).…”
Section: Teeth Objectsmentioning
confidence: 99%
“…VII: 5). Boar tusks with two holes, which could have been pendants or were sewn on the clothing, have been found from the grave dated to 900-750 BC in Przeczyce, Poland (Baron et al, 2022), and some pendants made of horse incisors have been found from Sobiejuchy (Harding et al, 2004, p. 64, pl. 28: 36-37).…”
Section: Teeth Objectsmentioning
confidence: 99%